Networking the yield curve: Implications for monetary policy - Tatjana Dalhaus; Julia Schaumburg; Tatevik Sekhposyan (European Central Bank (ECB), 2021)
We introduce a flexible, time-varying network model to trace the propagation of interest rate surprises across different maturities. First, we develop a novel econometric framework that allows for unknown, potentially asymmetric contemporaneous spillovers across panel units, and establish the finite sample properties of the model via simulations. Second, we employ this innovative framework to jointly model the dynamics of interest rate surprises and to assess how various monetary policy actions, for example, short-term, long-term interest rate targeting and forward guidance, propagate across the yield curve. We find that the network of interest rate surprises is indeed asymmetric, and defined by spillovers between adjacent maturities. Spillover intensity is high, on average, but shows strong time variation. Forward guidance is an important driver of the spillover intensity. Pass-through from short-term interest rate surprises to longer maturities is muted, yet there are stronger spillovers associated with surprises at medium- and long-term maturities. We illustrate how our proposed framework helps our understanding of the ways various dimensions of monetary policy propagate through the yield curve and interact with each other.
Keywords: C21; C53; E43; E44; E52; 330; Dynamic networks; Monetary policy; Yield-curve